2017
DOI: 10.1016/j.jpain.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in the Time Course and Magnitude of Changes in Circulating Neuropeptides After Pain Evocation in Humans

Abstract: This study tested the hypothesis that older adults would have a stronger response for substance P (facilitatory) but weaker response to β-endorphin (inhibitory), both in magnitude and time-course. Eight younger and 9 older adults underwent 3 experimental sessions using well-validated laboratory pain models: cold pressor task (CPT), contact heat pain (HP), and a non-painful control. Blood was collected through an indwelling catheter at baseline and 3, 15, 30, 45, and 60-minutes post-stimuli administration. Olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…A systematic review reported a lower pressure pain threshold in older adults, which suggested that old persons may be more sensitive to mechanically evoked pain . In addition, older adults had higher baseline levels of substance P and β‐endorphin, which could increase peripheral activity compared to that in younger adults . Therefore, older hypertrophic burn scar patients may experience more severe scar pain and paresthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review reported a lower pressure pain threshold in older adults, which suggested that old persons may be more sensitive to mechanically evoked pain . In addition, older adults had higher baseline levels of substance P and β‐endorphin, which could increase peripheral activity compared to that in younger adults . Therefore, older hypertrophic burn scar patients may experience more severe scar pain and paresthesia.…”
Section: Discussionmentioning
confidence: 99%
“…26 In addition, older adults had higher baseline levels of substance P and β-endorphin, which could increase peripheral activity compared to that in younger adults. 27 Therefore, older hypertrophic burn scar patients may experience more severe scar pain and paresthesia. However, in our study, the ORs for different ages were very close to 1 (1.046 and 1.038).…”
Section: Discussionmentioning
confidence: 99%
“…The neurotransmitters b-endorphin and SP [28,29] are vital in the pathophysiology of pain development. The concentrations of SP in serum of treatment groups were significantly lower than that of model group (Figure 12).…”
Section: Anti-inflammatory and Analgesic Effectsmentioning
confidence: 99%
“…Neuropeptides like beta-endorphin and substance P cannot cross the blood-brain barrier (Riley et al, 2017 ), making the cerebrospinal fluid (CSF) an ideal medium to investigate biochemical alterations relating to pain in the human brain. This study used CSF to determine the association between pain intensity, beta-endorphin and substance P levels, and post-anesthetic recovery duration (PARD) in active smokers and explore the factors related to postoperative pain intensity.…”
Section: Introductionmentioning
confidence: 99%